2021
DOI: 10.3389/fendo.2021.664657
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Yoga-Based Lifestyle Protocol (YLP) in Preventing Diabetes in a High-Risk Indian Cohort: A Multicenter Cluster-Randomized Controlled Trial (NMB-Trial)

Abstract: IntroductionThough several lines of evidence support the utility of yoga-based interventions in diabetes prevention, most of these studies have been limited by methodological issues, primarily sample size inadequacy. Hence, we tested the effectiveness of yoga-based lifestyle intervention against diabetes risk reduction in multicentre, large community settings of India, through a single-blind cluster-randomized controlled trial, Niyantrita Madhumeha Bharat Abhiyan (NMB). Research Design and MethodsNMB-trial is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
(91 reference statements)
1
9
0
Order By: Relevance
“…Study characteristics and descriptions of the interventions and main findings of eligible studies are summarised quantitatively in Table 1 , and qualitatively reviewed in the appendix (pp 14-23). The majority of the eligible studies were published in the last decade, 2012-2022, (90%), and conducted in lower-middle (56%) 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 or upper-middle-income (44%) 23 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 countries. No eligible study was found in low-income countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study characteristics and descriptions of the interventions and main findings of eligible studies are summarised quantitatively in Table 1 , and qualitatively reviewed in the appendix (pp 14-23). The majority of the eligible studies were published in the last decade, 2012-2022, (90%), and conducted in lower-middle (56%) 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 or upper-middle-income (44%) 23 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 countries. No eligible study was found in low-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…No eligible study was found in low-income countries. By continent, the vast majority of studies (84%) were performed in Asia (15 in India, 25 , 27 , 28 , 29 , 32 , 33 , 35 , 36 , 41 , 42 , 44 , 46 , 47 , 48 , 50 12 in China, 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 63 , 66 , 67 , 68 five in Iran, 31 , 37 , 40 , 43 , 45 two in Thailand, 51 , 65 Vietnam, 30 , 49 Bangladesh, 24 , 32 and Sri Lanka, 26 , 32 and one in Jordan, 69 Pakistan, 39 and Mongolia 38 ), followed (14%) by America (three in Brasil, 52 , 64 , 70 two in Colombia, 23 , 62 and one in Cuba 59 ), and only one study (2%) in Africa (Egypt 34 ). To define at-risk populations, most studies selected participants with impaired glucose/prediabetes (52%) or presenting a combination of cardiometabolic risks (34%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first protocol to be made specifically for the prediabetics and diabetics. The complete sequence of prayer, yogic postures, breathing and meditative techniques, along with specified time, was shown in previously published paper [ 24 ]. The Yogic practices were performed for 3 months for 60 min.…”
Section: Methodsmentioning
confidence: 99%